Amphibian's distribution in caves of the Sicó Massif - Soares, Joana Ferreira de Paiva Morais (2018)
Amphibians (salamanders, toads and frogs) are frequently found exploring karst environments, both at the surface and underground. This study aimed to approach both aspects through the evaluation of (a) the abundance and distribution of amphibians in caves of Sicó massif, central Portugal, and (b) the suitability of the water from Sicó massif sinkhole ponds and springs for amphibian’s early stages of development. Despite some studies reporting the presence of amphibians in European underground habitats, in Portugal there is a major lack of knowledge of these ecosystems, namely in the karst region. In order to provide further knowledge, several surveys were carried out in caves of the Sicó massif. Our main results document the observation of two species: Triturus marmoratus and Bufo bufo. Reports on these organisms are common in the underground habitats in Europe. However, in Portugal this is the first occurrence of both species in caves in central Portugal. Their presence might be due to searching for refuge and high humidity, escaping from predators, and accidental fall into cave entrances that might act as natural pitfalls. This research shows that the presence of amphibians in caves is underestimated and that more caves should be surveyed for the presence of amphibians in this particular massif, but also in other main karst areas in Portugal. Karst landscapes are threatened with pollution and contamination resultant from activities such as agriculture and industry, among others. Due to the scarcity of water on the surface, sinkhole ponds and springs are essential as breeding sites for these organisms. Considering these factors, we evaluated the effect of water collected from 6 different sites of Sicó massif in early stages of Hyla arborea. Through ecotoxicological essays, parameters such as survival, size, activity of antioxidant enzymes (GPx total, Se-dependent GPx, GRed and GST) and also lipidic peroxidation were evaluated. Complementarily, we determined several abiotic parameters and evaluated the presence of 6 pesticides. The results from both biomarkers evaluation and detection of pesticides show that in two sites conditions for larval development of amphibians may not be adequate. However, more studies are necessary to confirm these suspicions. Considering the relevance of these sites for conservation of various amphibian populations, further and complementary studies are necessary, namely for evaluating the effect of seasonality on water’s chemical parameters and the resulting effects of in situ exposure on larval stages.